Desensitizing treatments for dentin hypersensitivity: a randomized, split-mouth clinical trial - Veridiana Camilotti; Juliana Zilly; Priscilla do Monte Ribeiro Busato; Carlos Augusto Nassar; Patrícia Oehlmeyer Nassar (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The aim of this randomized, controlled, split-mouth, clinical study was to differentiate and clinically qualify the effectiveness of different desensitizing agents in the treatment of painful symptoms caused by cervical dentin hypersensitivity (CDH). Two hundred-and-fifty-two teeth of 42 patients were distributed into seven groups (n = 36): G1 - placebo; G2, G3, G4 and G6 - fluoride varnishes; G5 - sodium fluoride; G7 - potassium oxalate. Three applications were made one week apart. A three-score system (Alfa = 0, Bravo = 2, and Charlie = 3, respectively for no sensitivity, slight sensitivity and high sensitivity) was used to assess CDH after each application and after 30 days. The data were subjected to statistical analysis using the Kruskall-Wallis and Dun tests. After the second week, statistically significant differences were observed for all materials compared with the baseline. After 30 days, Group G7 had presented a significant gradual reduction along all the evaluated time intervals. It was concluded that all the desensitizing agents were capable of reducing dentin hypersensitivity, with the exception of the placebo and the sodium fluoride groups.